Growth Response of Robusta Coffee (Coffea canephora Pierre ex A. Froehner) Seedlings to the Application of Golden Apple Snail - Asmono, Sepdian Luri; Hutama, Adrian Cahya; Cinantya Anindita, Devina; Nugroho, Setyo Andi; Rahmawati, Rahmawati; Arifiana, Nisa Budi (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2026)
One type of coffee plant widely cultivated in Indonesia is robusta coffee. During cultivation, nursery practices are crucial for improving coffee quality and productivity. To obtain good Robusta coffee seedlings, fertilization is essential. The recommended fertilizer is organic, which is more environmentally friendly. Fertilizing with fermented golden apple snail extract supports sustainable agriculture. Therefore, the purpose of this study is to determine the concentration, frequency of treatment, and interaction on the growth of hybrid robusta coffee seedlings prolegitim (BP 42 x BP 358). The study was conducted in the field laboratory of Politeknik Negeri Jember for 5 months. This study used a non-factorial RBD with 7 treatments and 6 replications. K0 (Control-0% concentration); K1 (2.5% concentration + application every 4 weeks); K2 (5% concentration + application every 4 weeks); K3 (2.5% concentration + application every 2 weeks); K4 (7.5% concentration + application every 4 weeks); K5 (5% concentration + application every 2 weeks); K6 (7.5% concentration + application every 2 weeks). The observed variables include: Number of Leaves (pairs), Leaf Area Index, Stem Height, and Root Length. The experimental data were analyzed using ANOVA followed by the LSD test at the 5% significance level. The study found that the K2 treatment (5% concentration applied every 2 weeks) produced the optimal growth response, particularly in leaf area, seedling height, and root length.